Pengaruh pencucian daging ikan Patin (Pangasius hypophthalmus) setelah penggaraman terhadap jumlah mikroba dan citarasa wadi Patin - Restu Y Bakrie (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
Wadi is a semi-wet processed product from both livestock meat and fish through a process of salting, adding spices (sugar and samu) then followed by fermentation for a few days to produce a distinctive aroma and taste. The food fermentation process is traditionally carried out by several types of microorganisms that are synergistic, the microbes that play a role in fermentation products are lactic acid bacteria. Washing catfish meat after the salting process can accelerate the fish fementation process from 7 days to 3 days and reduce the salt content in fish meat from 1.13% (without washing) to 0.79% (washed) after a three-day fementation period. The best results of catfish wadi products in this study were C treatment with the following criteria: microbial (LAB) 6,5x104; organoleptic value (appearance, smell, taste and texture) = 7.64 on a hedonic scale. Keywords : Salting, washing, catfish wadi.